The Association between CHA2DS2-VASc Score with Increased Serum Creatinine Level in ACS Patients Undergoing PCI at RSUD dr. Saiful Anwar Malang - Fathoni, Emil; Widito, Sasmojo; Anjarwani, Setyasih; Satrijo, Budi; Putri, Valerinna Yogibuana Swastika (Heart Science Journal, 2023)
Background: The current literature on the relationship between the congestive heart failure, hypertension, age, diabetes mellitus, prior stroke or TIA or thromboembolism, vascular disease, age, sex category (CHA2DS2-VASc) score and increased Serum Creatinine (SCr) among Acute coronary syndrome (ACS) patients is noticeably limited in scope. Therefore, the primary objective of this study was to assess the correlation between CHA2DS2-VASc score with increased of Serum Creatinine in patients with ACS undergoing Percutaneous coronary intervention (PCI) procedures.Material and Methods: In this study, a total of 527 participants were recruited, comprising two groups: Increased SCr level (n=159) and normal SCr level (n=368). Data pertaining to clinical information and demographic characteristics, such as gender, age, diabetes mellitus (DM), hypertension (HT), congestive heart failure (CHF), history of stroke or transient ischemic attack (TIA), and vascular disease, were gathered from various sources, including registry data and medical records, diagnostic physical examination, electrocardiography and laboratory records. Logistic regression analysis was employed to assess the association between the CHA2DS2-VASc score and the incidence of increased SCr level.Result: In our study, we observed that the CHA2DS2-VASc scores were significantly higher in the group of patients who increase SCr level compared to those who did not increase SCr level. Furthermore, our Receiver Operating Characteristic (ROC) analysis revealed that a CHA2DS2-VASc score cutoff of 3 was determined to be the optimal threshold for estimating the increased SCr level (AUC= 0.805, 95% CI 0.762-0.848; p<0.01).Conclusion: The CHA2DS2-VASc score serves as a valuable tool for estimating the likelihood of SCr in patients undergoing PCI, offering a foundational assessment. Additionally, in PCI patients, an increase in the CHA2DS2-VASc score exceeding 3 is indicative of a heightened incidence of increased SCr level.